May 2015 - a climate change in UK politics - Hennig, B; Dorling, D (Wiley, 2015)
Look carefully at the map on page 21 and what do you see? Six large clumps of red in a gently rising blue sea, with a newly formed yellow beach to the north. Climate change in politics is both gradual and increases the chances of very stormy weather in the years ahead.